Timing of Tracheostomy in Intensive Care Unit Patients - Khammas,Ammar Hadi (2018)
Abstract Introduction The ideal timing of tracheostomy in intensive care units (ICUs) for critically ill patients undergoing prolonged mechanical ventilation (MV) is still a controversial issue. Objectives To determine the proper timing of tracheostomy and its impact on various clinical outcomes of adult patients in ICUs undergoing prolonged MV. Methods The present study consisted of a sample of 67 ICU adult patients who were submitted to open surgical tracheostomy and divided into two groups: 30 patients in the early tracheostomy (ET) group (within 1–10 days post intubation), and 37 patients in the late tracheostomy (LT) group (within 11–21 days post intubation). The correlation between the timing of tracheostomy of each group and various associated ICU clinical parameters were analyzed. Results The sample consisted of 61.19% male and 38.81% female patients, with a mean age of 47.263 ± 7.581 years. The mean MV duration in days was 7.91 ± 4.937 standard deviation (SD) in the ET group, and 15.32 ± 7.472 SD in the LT group (p= 0.001), with a mean sedation time of 6.13 ± 4.647 SD in the ET group, and of 11.98 ± 6.596 SD in the LT group (p= 0.001). The duration of the weaning process duration had a mean of 2.75 ± 2.586 SD days in the ET group, and of 5.39 ± 5.817 SD days in the LT group (p= 0.025), with a weaning failure rate of 28.57% in the ET group and 71.42% in the LT group (p= 0.01). The Mean ICU stay was 26.18 ± 4.732 SD in the ET group, and 11.98 ± 6.596 SD in the LT group (p= 0.879), and the incidence of ventilator-associated pneumonia (VAP) of 23.33% in the ET group and of 27.02% in the LT group (p= 0.15). Conclusion Early tracheostomy had a notable benefit in shortening the duration of the MV, lessening the sedation time and minimizing the risks of weaning failure, but it had no significant impact on both the overall duration of ICU stay and VAP incidence.